Exploring the Patterns Shaping Communication in the Turkish Construction Industry - Kunkcu, Handan; Koc, Kerim; Gurgun, Asli Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2025)
Communication among project team members is an indispensable requirement to provide momentum toward achieving efficiency, time, cost, quality, and safety targets in construction projects. Therefore, investigating the main patterns influencing communication in construction projects sheds light on hidden knowledge that can help improve project performance. This study aims to develop a framework that explains communication elements in construction projects with key communication constructs. To achieve the study objective, systematic literature review, bibliometric analysis, confirmatory factor analysis (CFA), and structural equation modeling (SEM) were used to probe the impact of each construct on communication and examine the importance level of the items. The model was developed based on five constructs (i.e., trust, attitude toward knowledge sharing, collaboration, reciprocal feedback, and social ties) comprising 26 items. Findings indicate that collaboration and trust are the most critical constructs, while the level of frequency in information exchange and consistent behavior of team members are the most vital items reflecting these constructs, respectively. The outcomes of this study are expected to enhance interpersonal communication abilities by considering the key indicators of communication patterns in construction projects.
Keywords: Communication; Collaboration; Confirmatory factor analysis; Structural equation modeling; Construction projects; COLLABORATIVE COMMUNICATION; SUPPLIER PERFORMANCE; FIT INDEXES; PROJECT; MANAGEMENT; INTENTION; VARIABLES; DESIGN; IMPACT; TEAMS; Engineering